2019
DOI: 10.12965/jer.1938124.062
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of inpatient cardiac rehabilitation for patients with treated left ventricular assist device in Korea: 1-year follow-up

Abstract: In Korea, the first patient with a left ventricular assist device (LVAD) for destination therapy had successful implantation of a continuous-flow model in 2012. We investigated the safety and efficacy of exercise therapy with LVAD implantation 15 Korean patients. We retrospectively reviewed 15 patients (mean age, 67.4±11.6 years; 10 males, 5 female, left ventricular ejection fraction 23.6%±7.1%), including 4 with implanted continuous-flow and 11 an axial-flow LVAD. The New York Heart Association functional cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Financial Costs and Resource Limitations: Broadly speaking, inadequate funding and resources both negatively influenced the ability to access and deliver ICR. 39 , 70 , 80 , 99 , 108 , 130 , 142 , 164 , 166 , 199 , 201 , 207 , 209–211 Vincent et al 145 and Schweikert et al 128 reported that it cost their institutions $4709 USD and €3388 EUR for total therapy charges per patient, respectively. Costs are significantly higher for those who require ICR in comparison to outpatient or community-based rehabilitation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Financial Costs and Resource Limitations: Broadly speaking, inadequate funding and resources both negatively influenced the ability to access and deliver ICR. 39 , 70 , 80 , 99 , 108 , 130 , 142 , 164 , 166 , 199 , 201 , 207 , 209–211 Vincent et al 145 and Schweikert et al 128 reported that it cost their institutions $4709 USD and €3388 EUR for total therapy charges per patient, respectively. Costs are significantly higher for those who require ICR in comparison to outpatient or community-based rehabilitation.…”
Section: Resultsmentioning
confidence: 99%
“…This often occurred when CR facilities and programs were limited and inaccessible, such as in rural regions. 39 , 70 , 80 , 99 , 108 , 130 , 142 , 164 , 166 , 199 , 201 , 207 , 209–211 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both domestic and international studies indicate that Phase I exercise rehabilitation can commence within the first 3 days post-LVAD implantation, specifically in the ICU. The initiation can occur as soon as the patient is awake and exhibits hemodynamic stability post-surgery [12][13][14]. For patients post-LVAD implantation during hospitalization, it is recommended to refer to the advanced intensive rehabilitation assessment and treatment plan from the University Hospitals Leuven Medical School [15].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Despite the number of LVADs implanted, safety data on CR participation and outcomes are limited to several small studies and a meta-analysis of 125 patients. [10][11][12][13][14][15][16][17][18][19][20] The purpose of the present analysis was to add to existing data and assess the outcomes of LVAD recipients referred for CR using a large, single-center continuous-flow LVAD cohort.…”
Section: Introductionmentioning
confidence: 99%